2017
DOI: 10.1002/yd.20230
|View full text |Cite
|
Sign up to set email alerts
|

Student Activism in the Technology Age

Abstract: This chapter discusses the emergent use of digital technology to inspire, connect, and sustain student activism on campus. An overview of student activism, opportunities, and challenges of this technology, along with recent case studies and implications for practice, are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Furthermore, another study reported that Twitter can positively provide students' active engagement in class when used for the educational purposes (Junco, 2012). Active social media and social networking platforms available for educational use in higher education can ensure that students benefit the available hashtags in communicating with their institutions and colleagues (Gismondi & Osteen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study reported that Twitter can positively provide students' active engagement in class when used for the educational purposes (Junco, 2012). Active social media and social networking platforms available for educational use in higher education can ensure that students benefit the available hashtags in communicating with their institutions and colleagues (Gismondi & Osteen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Social media has played an increasingly important role in social movements in recent years, facilitating instant communication and information-sharing among activists and between activists and other societal stakeholders [52][53][54]. This includes student activism, which has embraced social media as a new tool for campaigning and protesting [55,56]. Other research indicates that over 80% of FFD campaigns at HEIs in North America have a Facebook page and a host of other social media platforms are commonly used by campaigns [29].…”
Section: Methodsmentioning
confidence: 99%
“…Recent renderings of activism involve dismantling structures of oppression at the intersection of issues such as sexual assault and hatred against Black, lesbian, and transgender women (Krause et al, 2017;Renn, 2007). Whether the medium is face-to-face or online (Cabrera, Matias, & Montoya, 2017;Gismondi & Osteen, 2017), Black student leaders purposefully act to achieve the emancipation of marginalized people through social change movements. Bronfenbrenner's (1979Bronfenbrenner's ( , 1994Bronfenbrenner's ( , 2005 ecological paradigm was applied to examine how Black student leaders apply transgenerational knowledge as a form of racial socialization (Peters, 1985;Stevenson, 1994) to pursue social change through activist movements.…”
Section: Broad Definitions Of Black Identity Within the Home And Academementioning
confidence: 99%